The Analysis of Tourism Industry Strategies on Regional Original Revenue of Lampung Province - Agie Setiawan Chandra; Muhamad Emil Rachman (International Journal of Economics, Business and Innovation Research, 2024)
As one of the provinces in Indonesia, Lampung possesses natural and cultural potential that can be developed into tourist attractions. With its renowned tourist destinations, combined with a diversity of culture, arts, and religious elements, Lampung has reliable assets that are expected to drive economic growth and development. This study aims to identify strategies for enhancing local revenue through the tourism sector in Lampung Province. The research employs a descriptive qualitative method, utilizing data collection techniques such as interviews, observations, and questionnaires, and applies SWOT analysis. Based on positive findings, an aggressive growth-oriented policy is recommended. Improving security at tourist destinations is identified as a top priority strategy, thus requiring special attention from the Lampung Provincial Government. It is hoped that this research will assist the Lampung Provincial Government in increasing local revenue through the tourism sector.